Investment, Absorption of Manpower and Government Expenditure on Regional Original Income and Economic Growth - Dandy Ahmad Drajat; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (International Journal of Economics, Business and Innovation Research, 2023)
Literature study aims to analyze and determine the effect of direct and indirect effects of investment, employment and government spending on local revenue and economic growth. The results of literature studies from various journals found that: investment in local revenue and economic growth. In addition, employment also contributes positively to local revenue and economic growth. Meanwhile, government expenditure has varying effects depending on the type of expenditure observed. Government spending on infrastructure and human resource development has had a significant positive impact.